NUMERICAL MODELING OF THE 1998 PAPUA NEW GUINEA TSUNAMI USING THE COMCOT - Qonita, Zulfa; Karima, Shofia; Rusdiansyah, Alfi; Riyandari, Ritha (PATTIMURA UNIVERSITY, 2024)
The Papua New Guinea tsunami of 1998 is a unique phenomenon because the source of the tsunami propagation has been speculated. There was a 7.1-magnitude earthquake on July 17, 1998, at 18:49 WIT before the tsunami hit the Aitape area. However, previous studies have shown that the leading cause of the tsunami was not the earthquake but a submarine landslide. One of the steps to simulating the event is to do tsunami modeling. A tsunami propagation simulation will be conducted using Cornell Multi-grid Coupled Tsunami (COMCOT). This simulation was carried out with three scenarios to see which had the most significant effect on the tsunami event. The first scenario uses a tsunami source from a 7.1 magnitude earthquake, the following scenario is carried out using avalanche parameters, and the last scenario is a scenario with a combined source of earthquake and avalanche. The results of this study indicate that underwater landslides are the source of a tsunami similar to the original event.